Association between Serum Insulin and Interleukin-6 levels with Breast Cancer in Post-Menopausal Iraqi Women - Abd, Mohammed A.; Majeed, ٍShaymaa A. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Obesity rates are increasing day by day affecting all populations at different ages. The most prevalent kind of cancer among women worldwide is breast cancer, with increasing rates in the present time and the future. Substantial connections between obesity and breast cancer are demonstrated. Elevated circulating levels of insulin and interleukin-6 have a substantial link to obesity and breast cancer development.Objective: This study aimed to examine the serum levels of insulin and interleukin-6 in postmenopausal breast cancer patients and to study the connection between these biomarkers and breast cancer development.Method: In this research, 120 postmenopausal women actively participated: 30 had a body mass index of >30 kg/m2 diagnosed with breast cancer and considered as obese (group 1), 30 with a body mass index of 30 kg/m2 who were healthy and were obese (group 3), and 30 participants with a body mass index of